Dental Unit Waterlines: Disinfection and Management - Lakshman Samaranayake; Kausar Fakhruddin; Norbert Sobon; Thanaphum Osathanon (Elsevier, 2024)
Dental unit waterlines (DUWLs) are the conduits within the dental chair through which water derived from the municipal or other peripheral supply systems flows through the dental chair to reach the dental patient. The quality of the water so delivered must have a low pathogenic microbial burden so as to be safe for the patient and the dental personnel. Regulatory bodies have therefore set minimum standards for the quality of water that exits from DUWLs as part of routine infection control. Adopting a comprehensive approach that combines physical, chemical, and automated methodologies is recommended to effectively decontaminate DUWLs. This review discusses the complexities of DUWL decontamination in terms of (1) Best Practice Guidelines in dental healthcare settings to mitigate DUWL contamination, (2) origins of DUWL contamination and biofilm formation and the associated infectious risks, (3) contemporary approaches for minimizing DUWL contamination, and (4) constraints in combating biofilms in DUWLs. Compliance with regional and national regulations on DUWL decontamination is a legal obligation for all dental practitioners and fundamental to protecting public health.